1996
DOI: 10.1080/09670879609372014
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of stored grain insect pests in a wheat‐filled silo

Abstract: The distribution of insects in a wheat-filled large concrete silo was studied by drawing grain samples from the whole vertical depth by means of a special probe. The major insect species found were: Trogoderma granarium (Khapra beetle), Rhyzopertha dominica (Lesser grain borer), and Tribolium castaneum (Red flour beetle). Maximum activity of all species was found on the grain surface although some insects were found at all depths in varying numbers. Breeding activity of major insect pests was detected by incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Jian et al [37] found that adults of C. ferrugineus introduced in a 0.6-m diameter and 1.12-m high wheat column had a similar distribution with those introduced in 0.1 9 0.1 9 1.0 m columns. Inside elevator in the USA, the numbers of insects generally tended to decrease with the depth below the grain surface [23,24,52]. This suggests that insects infest wheat stored at the elevator after it has been loaded into bins and then disperse down into the grain [23].…”
Section: Insect Movement and Distributionmentioning
confidence: 99%
“…Jian et al [37] found that adults of C. ferrugineus introduced in a 0.6-m diameter and 1.12-m high wheat column had a similar distribution with those introduced in 0.1 9 0.1 9 1.0 m columns. Inside elevator in the USA, the numbers of insects generally tended to decrease with the depth below the grain surface [23,24,52]. This suggests that insects infest wheat stored at the elevator after it has been loaded into bins and then disperse down into the grain [23].…”
Section: Insect Movement and Distributionmentioning
confidence: 99%
“…The 9-fold difference in densities between adult and larval stages was small compared with the 37-fold difference in the number of sounds they produced. In another study that compared ratios of immatures to adults, mean immature to adult ratios were 488.5, 85.9, 71.8, 56.6, 55.8, 17.8, 11.2, 9.7, 5.5, 5.2, 4.4, 3.0, 1.9 in wheat samples from a grain elevator bin [ 223 ]. Thirteen locations had immatures but no adults.…”
Section: Introductionmentioning
confidence: 99%
“…Stored grain insects are one of the main causes of stored grain losses which may reach 9% in developed countries and 20% or more in developing countries (Phillips & Throne, 2010). Khabra beetle Trogoderma granarium Everts is one of the most important stored grain pests, the most dangerous and resistant to insecticides (Mahmood et al, 1996). It adapts to various environmental conditions, where larvae can survive for 23 months without food and enter into dormancy until the food is available.…”
Section: Introductionmentioning
confidence: 99%